Using games to make the process of learning sign language enjoyable and interactive - Escudeiro, Paula (2014)
The work presented in this paper consists in the development of a game to make the process of learning sign language enjoyable and interactive. In this game the player controls a character that interacts with various objects and non-player characters with the aim of collecting several gestures from the Portuguese Sign Language. This interaction is supported by data gloves and Kinect. These gestures can then be represented by the character. This allows the user to visualize and learn or train the various existing gestures. To improve the interactivity and to make the game more interesting and motivating, several checkpoints were placed along game levels. This will provide the players a chance to test the knowledge they have acquired so far on the checkpoints by performing the signs using Kinect. A High Scores system was also created as well as a history to ensure that the game is a continuous motivating process as well as a learning process.